Psychometric and Rash Analysis of the UCLA Loneliness Scale – 16 in a Portuguese Sample of Older Adults - Faustino, Bruno (2022)
Loneliness is a serious concern in modern societies, particularly among older adults, while being imperative that clinicians use reliable instruments for an accurate assessment of this problem. This study aims to describe a mixed statistical approach to assess the psychometric properties of the UCLA Loneliness Scale-16 in Portuguese old-aged individuals. The sample comprised 153 individ- uals (59.1% women and 40.3% men), aged 61–98 (M = 78.80, SD = 8.58). The psychometric properties of UCLA Loneliness Scale-16 were analyzed with explora- tory factorial analysis, internal consistency, convergent and divergent validity and through the item response theory. The results suggested a bidimensional structure for this instrument. The scale showed satisfactory psychometric properties with a high internal consistency. In addition, a negative relationship with constructs of social support and functionality was also observed. Overall results suggest that the UCLA Loneliness Scale-16 is a psychometric reliable measure to evaluate social loneliness in the Portuguese elderly population.